Improving the Hydraulic Capacity of the Namakwekwe Drain - Festous Habumugisha (Uganda Christian University, 2024)
Kiteso Cell in the Northern Division of Mbale City is gradually experiencing urbanisation due to its proximity to the city centre. This has resulted in increased surface runoff which overwhelms the primary drainage channel in the area. The Namakwekwe Drain, locally known as the Ngabito channel, forms the primary drain in Kiteso Cell and is approximately 755 m long, with irregular sections, some of which are stone pith-lined and others earthed. A reconnaissance survey to obtain channel attributes was conducted to investigate the probable cause of flooding in the area. The runoff generated in the area was determined by analysing the hydrological characteristics of the catchment. The 50-year return period design storm was used to analyse the hydraulic capacity of the Namakwekwe Drain to determine the inadequacies of the channel. Channel geometry modifications were carried out using modelling software to ensure adequate capacity to handle runoff and mitigate flooding with a proposed concrete-lined trapezoidal channel with an estimated cost of UGX 1.25 billion and an estimated benefit-cost ratio of 1.16 to be realised in ten (10) years thus making it a worthwhile investment.